Detection and Analysis of the Magnetic Field Component of the Electromagnetic Radiation from the Quasi-Brittle Fracture of Tile-Cement-bound-Granular Materials Slabs - Galotera, Christian James (Archīum Ateneo, 2020)
Current research reveals that the formation of micro-cracks during earthquake phenomena induces the emission of electromagnetic radiation (EMR). The EMR emitted during sudden events can be used as a hazard predictor for an upcoming earthquake. This study aims to measure the magnetic field component of the EMR during the actual fracture of a ceramic-tile cement-bound-granular-material (CBGM) slab in a laboratory setting. A comparison of the magnetic field emission with different CBGM was done. Six magnetic field sensors were optimally positioned around the concrete sample. Compressive stress was applied to the samples using an impact loader and a sound meter was used to verify the occurrence of the fracturing phenomenon. The time difference between signals was recorded to confirm the time delay between actual fracturing and EMR emission. Parameters such as cement ratio, material composition, material density, and concrete thickness were investigated to determine the effect on the magnetic field emitted. Results reveal that thicker concrete samples lead to lower magnetic field emissions while concrete with lower density results to higher magnetic field emissions. A time delay average of about 3s between the emission of sound and the magnetic field emission was observed regardless of the material composition. More extensive fracturing results to higher magnetic field emissions possibly due to the occurrence of greater crack density. This study proves that greater crack length formed during fracture resulted to higher magnetic field emissions since larger crack lengths result to more severed bonds. Results are generally in agreement with the Rabinovitch model.